Oncological Impact of M-Tor Inhibitor Immunosuppressive Therapy after Liver Transplantation for Hepatocellular Carcinoma: Review of the Literature - Tarantino, Giuseppe; Magistri, Paolo; Ballarin, Roberto; Di Francia, Raffaele; Berretta, Massimiliano; Di Benedetto, Fabrizio (Frontiers in Pharmacology, 2016)
Background: Hepatocellular Carcinoma (HCC) represents the fifth most common malignancy and the third cancer-related cause of death worldwide. Hepatitis B (HBV) and C (HCV) viral infections and alcohol abuse are the principal etiological factors for HCC. Liver transplantation (LT) is oncologically the preferable approach to HCC, as it can remove all the intrahepatic tumor foci, and also the oncogenic cirrhotic liver. The use of mTOR inhibitors (mTORi) for immunosuppression after LT for HCC has been proposed due to rapamycin antitumor activity. We decided to review the literature to clarify the oncological role of mTORi after liver transplantation for HCC, analyzing both present condition and future perspectives. Material and Methods: A systematic literature search was performed using PubMed, EMBASE, Scopus and the Cochrane Library Central. The search was limited to studies in humans and to those reported in the English language in the period of time between January 2005 and December 2015. Results: The literature search yielded 93 articles; after duplicates were removed, 77 titles and abstracts were reviewed. Most relevant data and papers are herein reported and discussed. Conclusions: So far, the use of mTORi is encouraging in terms of oncological outcomes for patients underwent LT for HCC, both for prevention and treatment of HCC recurrence although definitive data are still awaited.